Gray Platelet Syndrome-Unusual Presentation with Spontaneous Splenic Rupture: A Case Report and Literature Review - Duha I. Barghouthi; Lila H. Abu-Hilal; Yumna Njoum; Abeer Dar Hasan; Khaled Alshawwa; Fadi Hourani (SAGE Publishing, 2023)
Gray platelet syndrome (GPS) is a rare hereditary hemorrhagic disorder characterized by macrothrombocytopenia and the absence of alpha-granules in platelets. Clinically, mild-to-moderate bleeding is the main manifestation, often accompanied by thrombocytopenia, splenomegaly, and myelofibrosis. Here, we present a case of a 15-year-old male patient with a history of hepatosplenomegaly, and thrombocytopenia for 8 years, who presented with sudden generalized abdominal pain. Despite initial suspicion of gastroenteritis, diagnostic imaging revealed an extensive hemoperitoneum. Subsequent genetic testing confirmed the diagnosis of GPS, which had not been previously identified. This case highlights the importance of considering inherited platelet disorders should be considered in adolescents with long-standing thrombocytopenia, and emphasizes the need for thorough evaluation in patients with suggestive symptoms.